Rola podniebienia miękkiego w procesie rozwoju techniki wokalnej - Danel, Renata (Logopedia Silesiana, 2014)
What makes human voice unique among other instruments is the fact, that it is a liveinstrument which, as the only one, produces articulated tones. Among every all articulated organswhich are responsible for that phenomenon velum draws the highest attention. It is the moving andarticulating organ situated in the oral cavity. Good condition of the organ provides better articulationand resonance, elimination of rhinolalia and development of diapason for the vocalist. Theseelements are the quintessence of vocal technique. Belittling Underestimating velum’s efficiency leadsto many irregularities and faults excluding proper voice projection in the above named aspects.